Ascending aorta dilatation for pulmonary atresia with ventricular septal defect: a report of three adult cases - Zheng-Jie Zhang; Ming-Kui Zhang; Hui Xue; Li-Xin Fan (Journal of Cardiothoracic Surgery)
Abstract Background Patients with pulmonary atresia and ventricular septal defect (PA/VSD) are prone to progressive aortic dilation. However, there are relatively few reports of progressive development of aortic aneurysm or aortic dissection in adult patients who missed early corrective surgery. Presentation of cases Case 1: A 38-year-old man with PA/VSD and a bicuspid aortic valve (BAV), underwent VSD repair, aortic valve replacement, and PA correction at age 21. Seventeen years after surgery, an aortic dissection occurred in the ascending aorta, which subsequently underwent the Bentall procedure. Case 2: A 33-year-old male with PA/VSD, and a Nakata index of 31.24 mm2/m2, underwent a central shunt surgery at age 17. Sixteen years after surgery, an aortic root aneurysm and ascending aortic dilatation (AAD) developed. Case 3: A 42-year-old female underwent corrective surgery for PA/VSD repair at age 14. Twenty-eight years after surgery, an AAD developed. Conclusions Adult patients with PA/VSD who miss the optimal age for surgery are more likely to develop dilatation of the ascending aorta and are at risk for aortic dissection. Therefore, long-term follow-up and monitoring is needed in this patient population.